Community Asset Valuations by Non‐profit Government Entities. Issue 3 (23rd May 2018) - Czernkowski, Robert; Lim, Stephen
Abstract: This paper examines an implication of applying International Financial Reporting Standards to the government sector in Australia. We posit both a self‐interest and a transparency motivation for local governments effecting revaluations of both infrastructure assets and community land. The self‐interest motivation was expected to manifest as a relationship between the amount of revaluation and CEO (or management team) remuneration. The transparency motivation was expected to result in a relationship between revaluation and the extent of spending on these assets, measured as both the quantum of materials and contracts expense, and as the quantum of contracts awarded by the entity above the disclosure threshold. We also speculated that revaluations may be used to signal to state governments a need for additional funds through capital and/or operating grants. At conventional levels of significance, we find no support for these relationships, suggesting that agency motivations at the local government level are either more subtle or non‐existent. As local government authorities in our study follow a reporting framework and standardised accounting procedures prescribed by the state government (in compliance with applicable AASB/IFRS standards), financial and public accountabilities are also likely to be a driver for the valuation of local infrastructure assets at fair value, and this is not likely to be undermined by the opportunistic incentives we have considered. Abstract : We explore whether management compensation incentives and supply contracting incentives in local government authorities are related to asset revaluation behaviour. Finding no such relationship, we conclude that the lack of opportunistic self‐interest effects suggests that the application of an International Financial Reporting Standards framework to local government reporting is not at face value inappropriate.